Passing the dividend baton: The impact of dividend policy on new CEOs’ initial compensation - Goergen, Marc; Chen, Jie; Song, Wei (Elsevier, 2019)
We examine how firms’ dividend policy affects the initial compensation of their newly appointed CEOs. We focus on newly appointed CEOs to isolate the effect of dividends on compensation and to provide new insights into an aspect largely neglected by compensation research. We show that the dividend payout is positively related to new CEO compensation. Further, the positive effect of dividends is stronger for firms with no dividend cuts over the past two, three and four years, firms with relatively high institutional ownership, and those with strong boards, consistent with new CEOs receiving higher pay as compensation for greater dividend pressure.
Keywords: CEO compensation; New CEOs; Dividend policy; Corporate governance; 53 Ciencias Económicas; ODS 16 - Paz, justicia e instituciones sólidas